USE OF DRONES FOR SOLAR PANEL INSPECTION IN SOLAR PARKS: USE OF DRONES FOR SOLAR PANEL INSPECTION IN SOLAR PARKS - Dobrev, Stefan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The use of drones to inspect solar panels in solar parks has become one of the most effective, efficient, and safe approaches for maintaining and optimizing largescale photovoltaic (PV) installations.